Peruvian agro-export sector: a competitiveness study of its main products, 2014 - 2023 - Castro Sanchez, Claudia Alejandra De Jesus; La Rosa Salazar, Kiara Darell; Montes Tocto, Richard Ignacio; Collazos Alarcón, Mercedes Alejandrina (LACCEI, 2025)
This study analyzes the competitiveness of Peru’s main agro-export products in international markets (2014–2023), applying comparative and competitive advantage theories. Using a quantitative approach with specialization and competitiveness indicators, it evaluates internal and external factors affecting performance, identifies trends, and offers recommendations for improving the sector’s global positioning. Findings show that while grapes and asparagus remain competitive, products like avocado and coffee face growing challenges, requiring innovation and diversification. The study also underscores the potential of emerging products such as blueberries. This research fills a gap in systematized data and contributes to strengthening Peru’s role in international trade